Dampak Media Digital terhadap Komunikasi Politik - Ihsan, Abdi (Komunika : Jurnal Ilmiah Komunikasi, 2025)
This study investigates the impact of digital media on political communication in Indonesia. Political communication is not only a means to influence public opinion, mobilize support, and build a political image, but it is also the main foundation in shaping political mindsets and behaviors covering various aspects of people's lives. Digital media opens up possibilities for people to interact actively. The research method used in this study is a quantitative method that focuses on case studies in the context of political communication. Data collection was carried out using online surveys, social media content analysis, and interviews with political communication practitioners. The results of the study show that the use of social media in political campaigns has increased drastically in recent years. The use of digital media is able to effectively change voter behavior, stimulate active political participation, and influence the direction of a political campaign with all its elements. With information easily accessible via smartphones or computers, they can form their own opinions about potential leaders and easily interact with them. Overall, political campaigns through social media in the context of elections in Indonesia have shown a very positive impact.